Plasma apolipoprotein A1 as a biomarker for Parkinson disease. Issue 1 (6th August 2013) - Qiang, Judy K.; Wong, Yvette C.; Siderowf, Andrew; Hurtig, Howard I.; Xie, Sharon X.; Lee, Virginia M.‐Y.; Trojanowski, John Q.; Yearout, Dora; B. Leverenz, James; Montine, Thomas J.; Stern, Matt; Mendick, Susan; et al.
<x xml:space="preserve">Abstract</x> Objective To identify plasma‐based biomarkers for Parkinson disease (PD) risk. Methods In a discovery cohort of 152 PD patients, plasma levels of 96 proteins were measured by multiplex immunoassay; proteins associated with age at PD onset were identified by linear regression. Findings from discovery screening were then assessed in a second cohort of 187 PD patients, using a different technique. Finally, in a third cohort of at‐risk, asymptomatic individuals enrolled in the Parkinson's Associated Risk Study (PARS, n = 134), plasma levels of the top candidate biomarker were measured, and dopamine transporter (DAT) imaging was performed, to evaluate the association of plasma protein levels with dopaminergic system integrity. Results One of the best candidate protein biomarkers to emerge from discovery screening was apolipoprotein A1 (ApoA1; p = 0.001). Low levels of ApoA1 correlated with earlier PD onset, with a 26% decrease in risk of developing PD associated with each tertile increase in ApoA1 (Cox proportional hazards, p < 0.001, hazard ratio = 0.742). The association between plasma ApoA1 levels and age at PD onset was replicated in an independent cohort of PD patients (p < 0.001). Finally, in the PARS cohort of high‐risk, asymptomatic subjects, lower plasma levels of ApoA1 were associated with greater putaminal DAT deficit (p = 0.037). Interpretation Lower ApoA1 levels correlate with dopaminergic system vulnerability in symptomatic PD patients and in asymptomatic individuals with physiological reductions in dopamine transporter density consistent with prodromal PD. Plasma ApoA1 may be a new biomarker for PD risk. ANN NEUROL 2013;74:119–127